1995
DOI: 10.1136/adc.73.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors in the presence, severity, and triggers of asthma.

Abstract: The role of heredity in the presence of asthma, severity of the condition, and impact of 12 specific triggers of attacks was investigated. Health surveys containing questions about children's asthma characteristics were completed by 325 families with twin children across the United States. Data for 39 monozygotic twin pairs and 55 same sex dizygotic twin pairs who were between 2 and 20 years of age and had asthma present in at least one member of each pair were received and analysed. Results revealed higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Asthma is known to run in families, and studies also suggest that there is a considerable hereditary component for disease severity [3]. To date, there are few genetic studies on therapy-resistant asthma in children, and few studies have explored the gene expression profile that characterises this phenotype [4].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is known to run in families, and studies also suggest that there is a considerable hereditary component for disease severity [3]. To date, there are few genetic studies on therapy-resistant asthma in children, and few studies have explored the gene expression profile that characterises this phenotype [4].…”
Section: Introductionmentioning
confidence: 99%
“…The agedependent distribution of atopic disease and associated quantitative traits suggests a reduced penetrance of genetic susceptibility in early and later life. Twin studies have generally shown that concordance rates for asthma are significantly higher in MZ twins than in DZ twins (Hopp et al 1984;Duffy et al 1990;Nieminen et al 1991;Sarafino and Goldfedder 1995), whether reared apart or together (Hanson et al 1991). Broadsense heritability estimates derived from twin studies range from 36% (Nieminen et al 1991) to 75% (Duffy et al 1990).…”
Section: The Genetic Epidemology Of Asthma and Associated Traitsmentioning
confidence: 99%
“…Alguns estudos, incluindo com gêmeos 2 , têm mostrado que uma série de genes e seus polimorfismos influenciam os desenvolvimentos imune e pulmonar e a resposta a fatores ambientais, contribuindo para o aparecimento e/ou gravidade da asma. O gene fator de crescimento transformante-β 1 (TGF-β 1 ) está localizado no cromossomo 19q13 3,4 .…”
unclassified